2007
DOI: 10.1007/s11199-007-9216-2
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Men of Color to a Commonly Used Rape Prevention Program: Attitude and Predicted Behavior Changes

Abstract: African American, Latino, and Asian first-year college men (36) saw The Men's Program, an all-male rape prevention workshop, and wrote answers to four openended questions to determine how men from non-white groups react to a commonly used rape prevention program. Using a multi-stage inductive analysis, participant responses fell into five main themes including reinforced current beliefs and/or no changes, increased awareness of rape and its effects on survivors, increased understanding of consent, plans to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Non‐White students were more likely to be “cheerleaders” for the program, and in doing so they expressed somewhat stronger support for the program than did White students. This is consistent with previous research indicating that Black college students report greater interest in sexual health education than do White college students (Gerend & Magloire, ); however, some research indicates otherwise (Foubert & Cremedy, ; Foubert, Godin, & Tatum, ). Our findings suggest that the structural disadvantages non‐White students experience may be associated with the extent to which they support campus sexual assault educational efforts.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Non‐White students were more likely to be “cheerleaders” for the program, and in doing so they expressed somewhat stronger support for the program than did White students. This is consistent with previous research indicating that Black college students report greater interest in sexual health education than do White college students (Gerend & Magloire, ); however, some research indicates otherwise (Foubert & Cremedy, ; Foubert, Godin, & Tatum, ). Our findings suggest that the structural disadvantages non‐White students experience may be associated with the extent to which they support campus sexual assault educational efforts.…”
Section: Discussionsupporting
confidence: 90%
“…A few studies indicate that, compared to heterosexual men, heterosexual women have more factual knowledge of what constitutes consensual sexual activity and that students who lack an understanding of what constitutes consensual sex have higher rape myth acceptance (Heppner, Humphrey, Hillenbrand-Gunn, & DeBord, 1995;Jozkowski & Peterson, 2013). In addition, there is evidence that non-White male students, fraternity members, and male athletes benefit from educational efforts focused on increasing their understanding of consent (Foubert & Cowell, 2004;Foubert & Cremedy, 2007). Beyond this, however, no existing studies, to our knowledge, have identified how variations in consent knowledge affect issues such as perceptions about sexual assault.…”
Section: Intersectionality and Student Awareness Of Sexual Assaultmentioning
confidence: 99%
“…Although Foubert and Masin did not test if the effectiveness of the program varied by ethnicity, it was found to be effective in a small sample (n = 36) of African American, Latino, and Asian American college men (Foubert & Cremedy, 2007).…”
mentioning
confidence: 90%
“…Unfortunately, the studies have focused on fairly homogenous populations: Caucasian college students or military-enrolled males. Foubert and Cremedy (2007) examined whether a group of African American, Latino, and Asian college students reported attitude change after being exposed to The Men's Program. After exposing 36 participants to the intervention, they were asked to answer several open-ended questions to determine how men from "non-white" groups differ in their responses.…”
Section: The Men's Programmentioning
confidence: 99%